Comparing natural and synthetic polymeric nanofluids in a mid-permeability sandstone reservoir condition - Augustine, Agi; Radzuan, Junin; Gbadamosi, Afeez; Muhammad, Manan; Mohd Zaidi, Jaafar; Mohammed Omar, Abdullah; Agus, Arsad; Nur Bashirah, Azli; Muslim, Abdurrahman; Yakasai, Faruk (Elsevier B.V., 2020)
Biopolymeric nanofluids have been proposed as an eco-friendly substitute to synthetic polymeric nanofluids to cut cost and environmental effect. However, previous studies on the use of biopolymeric nanofluids to enhance oil recovery focused only on adsorption and fluid injectivity at ambient condition. In this study, the thermal degradation of crystalline starch nanofluid (CSNF) at reservoir condition was investigated and compared with silica and aluminium oxide polymeric nanofluids, SiO2PNF and Al2O3PNF respectively. The thermal degradation of the polymeric nanofluids was investigated using Brookfield RST rheometer. Moreover, interfacial tension (IFT) properties and wettability alteration efficiency of the polymeric nanofluids were determined using Easy Dyne KRUSS tensiometer and sessile drop technique, respectively. Finally, the oil displacement ability of the polymeric nanofluids at typical reservoir condition was studied using Fars EOR technologies high-pressure high-temperature apparatus. Experimental result shows that the viscosities of SiO2PNF and Al2O3PNF decreased with increase in temperature, whereas the viscosity of CSNF increased with temperature. Besides, CSNF exhibited a significant decrease in IFT at all conditions investigated while IFT results of SiO2PNF and Al2O3PNF showed a non-monotonic trend with increase in temperature. Moreover, CSNF showed better potential to alter wettability at all conditions. The microscopic image of the emulsion generated shows stability of the emulsion over a long period and confirmed the ability of CSNF to withstand high temperature degradation compared to SiO2PNF and Al2O3PNF. Finally, it was observed that the mobility ratio of water flooding approaches unity faster than that of SiO2PNF, Al2O3PNF and CSNF, respectively. It can be concluded from this study that 13–23% incremental oil recovery can be achieved with the use of polymeric nanofluids.